2020
DOI: 10.3390/su12031080
|View full text |Cite
|
Sign up to set email alerts
|

Development and Investigation of a New Low-Cement-Consumption Concrete—Preplaced Aggregate Concrete

Abstract: Reducing consumption of cement in concrete will achieve huge benefits in decline of carbon emission, conservation of natural resources and reduction of the cost of concrete. In this paper, the low-cement-consumption concrete, preplaced aggregate concrete (PAC), is prepared and 12 types of mixtures including four water–binder ratios (W/B) and three sand–binder ratios (S/B) are designed to detect the effect of W/B and S/B on the mechanical properties and failure mechanism of PAC. Experimental and analytic result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In order to determine the compressive strength of concrete, 18 samples were tested, while the remaining ones were subjected to thermal tests. Preplaced aggregate concrete is prepared by placing coarse aggregate into formworks and then injecting the grout mortar into the void between the coarse aggregate [ 33 ]. The composition of the mix is presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the compressive strength of concrete, 18 samples were tested, while the remaining ones were subjected to thermal tests. Preplaced aggregate concrete is prepared by placing coarse aggregate into formworks and then injecting the grout mortar into the void between the coarse aggregate [ 33 ]. The composition of the mix is presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…According to the research of Rajabi et al [ 6 ], preplaced aggregate concrete outperformed ordinary concrete in terms of compressive strength, tensile strength, Young’s modulus, ultrasonic pulse velocity, and Schmidt hammer rebound number. Lv et al [ 13 ] reported that the preplaced aggregate concrete’s cubic compressive strength, splitting tensile strength, and elastic modulus all decreased when the ratio of water to binder and sand to binder increased. The elastic modulus of preplaced aggregate concrete might be increased by up to 20% when compared to conventional concrete at identical compressive strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The first involves placing coarse aggregate into formworks while the second is injecting the potential grout into the void [1]. This method provides several benefits compared to the conventional concrete due to its flowability, absence of internal vibration, lower energy consumption, and cement weight [2][3][4]. However, one of the essential factors affecting PAC Technology is the quality of coarse aggregate and grout especially due to the influence of several factors such as the type of sand, cementsand ratio composition, water-cement ratio, and cement for conventional grout [5,6].…”
Section: Introductionmentioning
confidence: 99%